THE MORPHOMETRY AND SEX RATIO OF Gerris marginatus Say (HETEROPTERA: GERRIDAE) IN TROPICAL AREA - Watiniasih, Ni Luh (Bumi Lestari Journal of Environment, 2016)
Gerris marginatus is one fresh water insect distributed from temperate to tropical areas. It can be found in almost every freshwater biotope, making them excellent objects for ecological and biogeographic studies.  Most recent studies found that this water insect was one good candidate for examining the effect of fresh water pollution.  This species shows morphometric differences between male and female, but there has no studies examining this morphometric differences particularly in tropical areas.  This study aimed to determine and investigate the morphometric differences between male and female and their sex ratio of G. marginatus in one of freshwater body in Bali.   Samples were collected from Jangu River at Karangasem Regency on February 2014.  Samples were preserved in 70 % awaiting for identification and further studies. Identification was performed at Animal Taxonomy Laboratory, Biology Department. The results show that there were morphometric differences between male and female of G. marginatus in tropical area.  Males were significantly larger of many variable measured compared to females. However, they also exhibit sex ratio bias toward females.
Keywords: morphometric, sex ratio, water strider, Gerris marginatus